ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK KOPI DAN KUALITAS PELAYANAN MENGGUNAKAN METODE IMPORTANCE PERFOMANCE ANALYSIS (Studi Kasus Di Geo Coffee) - Ranitaswari, Putu Anggi; Mulyani, Sri; Bayu Sadyasmara, Cokorda Anom (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
This study aims to determine the attributes that are considered important by consumers in order to achieve customer satisfaction, know the level of satisfaction or level of consumer suitability of products and services in Geo Coffee, and determine the attributes that need to get priority from the company to be improved in order to achieve customer satisfaction . This research was conducted at Geo Coffee. The sample used was 91 respondents using epurposive sampling method. Data were obtained by distributing questionnaires and correspondents directly. This research uses Importance Performance Analysis method. The result of this research shows that attribute with highest level of consumer satisfaction for product quality is characteristic of coffee taste characteristic based on brand cafe with level of matching equal to 101.95%. the attribute with the lowest level of conformity is a constant (stable) coffee taste for each presentation corresponding to a suitability level of 82.52%. Attributes with the highest level of customer satisfaction for service quality is the speed in responding to complaints and customer problems with a level of suitability of 120.34%. The attribute with the lowest level of customer satisfaction for service quality is the waiter providing services and appropriate handling to customer needs with the level of suitability of 80.05%. The attributes that must be prioritized for the product are the constant (stable) coffee taste of each serving and the sweet taste of coffee. The attributes that must get priority for service is the process of making order menu in Geo Coffee done quickly. Keywords : customer satisfaction, Importance Performance Analysis, Geo Coffee